(untitled) (Bangladesh Journal of Agricultural Research, 2016)
Field studies were carried out to evaluate the efficacy of four new generation insecticides along with a botanical against mustard aphid (Lipaphis erysimi Kalt.) and their toxicity to coccinellid beetles and foraging honeybees during 2014-15 at Bangladesh Agricultural Research Institute (BARI), Gazipur, Bangladesh. Buprofezin 40 SC was found to be the most effective against aphid offering the lowest aphid population (1.56/ top10cm central twig) at 7 days after spraying (DAS) which was statistically identical to Diafenthiuron 500SC (1.85/ top10cm central twig). Among the treatments, Azadiractin 1EC appeared to be safest to coccinellid beetles and foraging honeybees because it recorded the highest number of beetle (7.50 /5 plants) and honeybee (9.64 /plot/5 min) population at 7 DAS, although honeybee population did not vary statistically with that of Buprofezin 40 SC and Lufenuron 5EC treated plots. Indoxacarb 145SC was found to be the most toxic against honeybees. However, the highest yield was obtained from Buprofezin 40 SC (1.57 t ha-1) treated plot although this was statistically identical to that Diafenthiuron 500SC (1.52 t ha-1) and Azadiractin 1EC (1.48 t ha-1) treated plots. Bangladesh J. Agril. Res. 41(4): 725-734, December 2016